Repurposing of the β-Lactam Antibiotic, Ceftriaxone for Neurological Disorders: A Review - Yimer, Ebrahim M.; Hishe, Hailemichael Zeru; Tuem, Kald Beshir (Frontiers in Neuroscience, 2019)
So far there is no cure or disease-modifying agents available for most of the well-known neurological disorders and therapy is typically focused on relieving symptoms and supportive care to improve the quality of life of the patients. Besides, the traditional de novo drug discovery technique, particularly for neurological disorders, is more challenging hence repurposing of existing drugs for these conditions are supposed to be an efficient and dynamic approach that can substantially reduce the investment spent during drug development. Currently, there is emerging evidence that suggests the potential of a beta-lactam antibiotic, ceftriaxone to alleviate the symptoms of different experimentally-induced neurological disorders, such as Parkinson’s disease, Alzheimer’s disease, amyotrophic lateral sclerosis, epileptic-seizure, brain ischemia, traumatic brain injuries, and neuropathic pain. Ceftriaxone also affects the markers of oxidative status and neuro-inflammation, glutamatergic systems as well as various aggregated toxic proteins involved in the pathogenesis of different neurological disorders. Moreover, ceftriaxone administration to animal models of drug dependency was found to improve the withdrawal symptoms upon drug discontinuation. Thus, this review aimed to describe the effects of ceftriaxone against multiple models of neurological illnesses, drug dependency, and withdrawal. It also emphasizes the possible mechanisms of neuroprotective actions of ceftriaxone with respective neurological maladies.